Analytical authentication of organic products: an overview of markers. (15th October 2012) - Capuano, Edoardo; Boerrigter‐Eenling, Rita; van der Veer, Grishja; van Ruth, Saskia M
Abstract: Consumers' interest in organic foods is increasing and so is the need for robust analytical tools for their authentication. This review focuses on the most promising biomarkers/analytical approaches that are available for the authentication of organic produce. Food products have been subdivided into two groups: foods of plant origin (crops) and foods of animal origin (meat, milk and dairy products, eggs and fish). For each food category the most suitable biomarkers are presented and their potential for authentication is discussed. In the light of current knowledge, it is unlikely that the authentication of organic food products can be attained by the measurement of a single marker. Analytical approaches based on the measurement of multiple markers and/or complex chemical or physical profiles/fingerprints supported by multivariate statistical analysis seem considerably more promising in this respect. For the development of robust classification models, well‐designed experimental studies must be performed that rely on data sets that are both well balanced and of sufficient size to ensure that all relevant sources of variation for the target biomarkers are included in the reference database. Copyright © 2012 Society of Chemical Industry